2009
DOI: 10.1158/1535-7163.mct-09-0300
|View full text |Cite
|
Sign up to set email alerts
|

Combination of EGFR and MEK1/2 inhibitor shows synergistic effects by suppressing EGFR/HER3-dependent AKT activation in human gastric cancer cells

Abstract: EGFR tyrosine kinase inhibitors have shown promising efficacy in the treatment of tumors with EGFR mutations and amplifications. However, tyrosine kinase inhibitors have also proven ineffective against most tumors with EGFR wild-type (WT) alleles. Although some genetic changes, including the KRAS mutation, have been shown to confer resistance to tyrosine kinase inhibitors, novel strategies for the treatment of cancer patients with tumors harboring EGFR WT alleles have yet to be thoroughly delineated. The princ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 43 publications
(72 reference statements)
7
61
0
Order By: Relevance
“…The molecular alteration of these cells was previously reported (19). SNU216 and NCI-N87 cells were sensitive to saracatinib at IC 50 values lower than 1 mmol/L ( Table 1).…”
Section: Snu216 and Nci-n87 Gastric Cancer Cells Were Sensitive To Sasupporting
confidence: 73%
“…The molecular alteration of these cells was previously reported (19). SNU216 and NCI-N87 cells were sensitive to saracatinib at IC 50 values lower than 1 mmol/L ( Table 1).…”
Section: Snu216 and Nci-n87 Gastric Cancer Cells Were Sensitive To Sasupporting
confidence: 73%
“…1 and 2). These results are in accordance with previous reports (43,44). Furthermore, we showed that U0126 upregulates IGF-Iand EGF-stimulated phosphorylation of IGF-IR and EGFR.…”
Section: Discussionsupporting
confidence: 94%
“…The MEK inhibitor has been found to exert efficacy against KRASmutant cancer cell lines that are resistant to gefitinib. A combination of MEK and EGFR inhibitors showed synergistic effects via inhibition of the EGFR/HER3/AKT pathway activated in MEK inhibitor-resistant cells (34). Moreover, the combination of RAD001 plus trastuzumab was more effective than either drug alone, suggesting inhibition of PI3K and mTOR is required for the growth-inhibitory effect of HER2 antagonists (50).…”
Section: Discussionmentioning
confidence: 99%
“…The growth-inhibitory effects of PF00299804 in a panel of 11 gastric cancer cell lines (SNU-1, 5, 16, 216, 484, 601, 620, 638, 668, 719, and N87), of which genetic status was previously reported, were examined (34). Interestingly, only HER2-amplified gastric cancer cells (SNU216 and N87) were sensitive to PF00299804 with a low range of IC 50 values (0.002-0.008 mmol/L).…”
Section: Her2 Amplification Is Highly Correlated With Sensitivity To mentioning
confidence: 99%